(untitled) - Minot, Nicholas (Hà Nội, 2004)
In Vietnam, where regional disparities in poverty are large, information about the spatial distribution of poverty is especially important because it helps policymakers and program designers understand the causes of poverty and target programs to the poorest regions. This study pro-vides estimates of poverty and inequality for small areas of Vietnam and explores the geographic determinants of poverty.
Keywords: Poverty,Economic geography,Nghèo đói; Vietnam,Vietnam,Việt Nam